A pilot study on the test re-test and the inter-rater reliability of the Melbourne Assessment of Unilateral Upper Limb Function - P. Jayaraman; T. Puckree (AOSIS, 2009)
Objective: The Melbourne Assessment of Unilateral Upper Limb Function(commonly referred to as the Melbourne A ssessment) was identiﬁed as atool to quantify the quality of upper extremity function in children with cerebral palsy aged 5 to 15 years in South Africa. Since the tool was nottested in a South African population before, it became necessary to determine its inter-rater and test-retest reliability.Methods: Five South African Black children with hemiplegic cerebral palsy served as the test sample. The raters were 2 neurodevelopmental trained physiotherapists with more than 2 and 8 years of experience in pediatric physiotherapy but novice to the use of the Melbourne Assessment. Both therapists acquainted themselves with the tool kit and manual prior to the rating. The entire assessment of each child was video taped and reassessed a week later by one of the therapists for test-retestreliability. Results: Ratings of the 2 raters and test-retest scores were correlated using the weighted Kappa due to the small sample size. Kappa scores for individual scores for interrater reliability and test-retest was 0, 75 and that for the totalscores were 0, 72 and 0, 82 respectively. Conclusion: These ﬁndings suggest that good inter-tester and test-retest reliability can be achieved for the MelbourneA ssessment when used in a group of South African Black children.